Respuesta :
Here's my thinking: If z<7, then z-7 is negative, and |z-7| is positive. So, with the understanding that z-7 is positive, the first part of this expression becomes:
7-z for z<7
Similarly: if z<7, then z-9 is negative and |z-9| is positive. Thus, -|z-9| is equivalent to (9-z).
|z−7|−|z−9|, if z<7 becomes (7-z) - (9-z) for z<7. Simplifying this, we get:
7 - z - 9 + z = -2
7-z for z<7
Similarly: if z<7, then z-9 is negative and |z-9| is positive. Thus, -|z-9| is equivalent to (9-z).
|z−7|−|z−9|, if z<7 becomes (7-z) - (9-z) for z<7. Simplifying this, we get:
7 - z - 9 + z = -2
Using the definition of the absolute value function, it is found that the expression for z < 7 is:
[tex]|z - 7| - |z - 9| = -2[/tex]
The definition of the absolute value function is:
[tex]|f(x)| = f(x), x \geq 0[/tex]
[tex]|f(x)| = -f(x), x < 0[/tex]
Then, for |z - 7|.
[tex]z - 7 \geq 0[/tex]
[tex]z \geq 7[/tex]
Then:
[tex]|z - 7| = z - 7, z \geq 7[/tex]
[tex]|z - 7| = -z + 7, z < 7[/tex]
For |z - 9|.
[tex]z - 9 \geq 0[/tex]
[tex]z \geq 9[/tex]
Then:
[tex]|z - 9| = z - 9, z \geq 9[/tex]
[tex]|z - 9| = -z + 9, z < 9[/tex]
Working with z < 7, we have that:
[tex]|z - 7| = -z + 7[/tex]
[tex]|z - 9| = -z + 9[/tex]
Then:
[tex]|z - 7| - |z - 9| = -z + 7 - (-z + 9) = -z + 7 + z - 9 = -2[/tex]
A similar problem is given at https://brainly.com/question/24514895